VD_FINDINFO Décision / 2015 / 609 vom 13. August 2015 - VD Tribunal cantonal (2015)
DÉTENTION PROVISOIRE, RISQUE DE RÉCIDIVE, RISQUE DE COLLUSION | 221 al. 1 let. b CPP (CH), 221 al. 1 let. c CPP (CH)